High-fat and high-cholesterol diet decreases phosphorylated inositol-requiring kinase-1 and inhibits autophagy process in rat liver - Hisao Naito (Nature Portfolio, 2019)
Abstract Precise molecular pathways involved in the progression of non-alcoholic steatohepatitis (NASH) remain to be elucidated. As Mallory–Denk bodies were occasionally observed in the enlarged hepatocytes in NASH model rat (SHRSP5/Dmcr) fed high-fat and high-cholesterol (HFC) diet, we aimed to clarify the roles of autophagy and endoplasmic reticulum (ER) stress in NASH progression. Male SHRSP5/Dmcr were randomly divided into 4 groups. Two groups were fed a control diet; the other two groups were fed a HFC diet for 2 and 8 weeks, respectively. The HFC diet increased the autophagy-related proteins levels and microtubule-associated protein 1 light chain 3-II/I ratio after 2 and 8 weeks, respectively. However, regarding ER stress-related proteins, the HFC diet decreased the levels of phosphorylated (p-) inositol-requiring kinase-1 (p-IRE-1) and p-protein kinase RNA-like ER kinase after 2 weeks. Additionally, the HFC diet increased anti-ubiquitin-positive cells and the level of the autophagy substrate p62, suggesting that the HFC diet induced dysfunction in ubiquitin-dependent protein degradation pathways. In conclusion, the HFC diet arrested the autophagy process in the liver; this was particularly associated with decreases in p-IRE-1 expression.